Multimorbidity and out-of-pocket expenditure on medicine in Europe: Longitudinal analysis of 13 European countries between 2013 and 2015 - Palladino, Raffaele; Pan, Tianxin; Mercer, Stewart W.; Atun, Rifat; McPake, Barbara; Rubba, Fabiana; Triassi, Maria; Lee, John Tayu (Frontiers in Public Health, 2023)
Background: Many European Health Systems are implementing or increasing levels of cost-sharing for medicine in response to the growing constrains on public spending on health despite their negative impact on population health due to delay in seeking care. Objective: This study aims to examine the relationships between multimorbidity (two or more coexisting chronic diseases, CDs), complex multimorbidity (three or more CDs impacting at least three different body systems), and out-of-pocket expenditure (OOPE) for medicine across European nations. Methods: This study utilized data on participants aged 50 years and above from two recent waves of the Survey of Health, Ageing, and Retirement in Europe conducted in 2013 (n=55,806) and 2015 (n=51,237). Pooled cross-sectional and longitudinal study designs were used, as well as a two-part model, to analyse the association between multimorbidity and OOPE for medicine. Results: The prevalence of multimorbidity was 50·4% in 2013 and 48·2% in 2015. Nearly half of those with multimorbidity had complex multimorbidity. Each additional CD was associated with a 34% greater likelihood of incurring any OOPE for medicine (Odds ratio=1·34, 95% CI=1·31 - 1·36). The average incremental OOPE for medicine was 26·4 euros for each additional CD (95% CI=25·1 - 27·7), and 32·1 euros for each additional body system affected (95% CI 30·6 - 33·7). Conclusion: Between 2013 and 2015 in 13 European Health Systems increased prevalence of CDs was associated with greater likelihood of having OOPE on medication and an increase in the average amount spent when one occurred. Monitoring this indicator is important considering the negative association with treatment adherence and subsequent effects